6(t+2)-76=-142

Simple and best practice solution for 6(t+2)-76=-142 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(t+2)-76=-142 equation:


Simplifying
6(t + 2) + -76 = -142

Reorder the terms:
6(2 + t) + -76 = -142
(2 * 6 + t * 6) + -76 = -142
(12 + 6t) + -76 = -142

Reorder the terms:
12 + -76 + 6t = -142

Combine like terms: 12 + -76 = -64
-64 + 6t = -142

Solving
-64 + 6t = -142

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '64' to each side of the equation.
-64 + 64 + 6t = -142 + 64

Combine like terms: -64 + 64 = 0
0 + 6t = -142 + 64
6t = -142 + 64

Combine like terms: -142 + 64 = -78
6t = -78

Divide each side by '6'.
t = -13

Simplifying
t = -13

See similar equations:

| 9x+17=3x-29 | | 2x-x+45=5 | | 2x-x+45= | | 6x+24=15x-75 | | -6x^3-19x^2-10=0 | | 2x+80=7x-85 | | 60-2x=9x-16 | | 2x^2+3x-14x=0 | | 131-7x=20x+17 | | 7x^2+2x-3=0 | | 3(x-4)=21 | | 8n+2-n=16 | | 217-6x=30x+21 | | -(7-4x)=18 | | 14-9x=166-37x | | -2(56-5)= | | 2-(x+4)=-2(x+1)-3 | | 5y-6x=0 | | x-15+x(x-15)=x | | 78-5x=10+18 | | 78-5x=10x-18 | | 4x+27=11x-50 | | 4x-27=11x-50 | | 4x-16=-8 | | -7x=-2x-65 | | 5(6z-1)-3(z+9)=24(z+1) | | 7y^2-y+9=0 | | x+7=10-2x | | 3x+16=-15 | | -6z+15-9z^2=0 | | 2(5x-6)=4(3+8) | | 15n^2-n-2=0 |

Equations solver categories